Pseudobombax furadense (Bombacoideae, Malvaceae), a new species from the Caatingas Domain, Brazil - Gianasi, Fernanda Moreira; Santos, Rubens Manoel Dos (Phytotaxa, 2022)
A new species of Pseudobombax (Bombacoideae, Malvaceae) is described from the Furados, Caatingas Domain, Brazil. The new species is morphologically similar to Pseudobombax simplicifolium but differs by the obovate, elliptic, depressed obovate or orbicular leaflets, the presence of branched trichomes on terminal branches, leaf primordia, petioles, adaxial and abaxial surfaces of leaflets, pedicel, bracteoles, and outer surface of the calyx, lepidote ovary, and the subglobose to ovoid, and spotted seeds.